Photoprotective lip formulation optimization methods: A systematic review - Imelda Matruty; Dzakiyya Nur Dhiya; Garnadi Jafar; Fenti Fatmawati (Institute of Computer Science (IOCS), 2026)
Photoprotective lip preparations such as balms and tints containing natural ingredients are increasingly being developed as an alternative protection against ultraviolet radiation. The complexity of the formulation composition requires an appropriate optimization method to produce products with optimal effectiveness and stability. This review aims to analyze and compare optimization of various methods used in photoprotective lip preparations, evaluating their advantages and limitations in determining optimum conditions. This study uses a systematic review approach by searching scientific articles from databases like Google Scholar and other relevant sources within a specific time frame of years. The extracted data includes active ingredient type, optimization method, formulation variables, trial numbers, and response parameters like Sun Protection Factor (SPF), pH, and physical properties. Analysis results show that optimization methods based on experimental design, such as Response Surface Methodology (RSM), provide superior and robust capabilities in evaluating variable interactions and modeling nonlinear relationships to determine optimum conditions simultaneously. In contrast, conventional methods like one factor at a time (OFAT) combined with ANOVA still dominate but have limitations in evaluating variable interactions and generating predictive models. Most studies report that material composition variations, particularly wax bases and active ingredients, significantly influence the formulation's SPF value and physical characteristics. Experimental design-based optimization methods, particularly RSM, are strongly recommended for developing photoprotective lip formulations because they provide more efficient, accurate, and predictive results. However, their practical application is still limited. Therefore, further research is greatly needed to increase the widespread adoption of this advanced method in developing future natural product-based innovative pharmaceutical preparations.